IDEAS OF HUMANITY IN CENTRAL ASIAN SUFIS - Bozorov M (International Journal of Psychosocial Rehabilitation, 2020)
The Renaissance in Central Asia dates back to the IX-XII centuries. The Renaissance is characterized by a serious focus on the issues of human enlightenment, spirituality, morality, and humanity. During this period the direction of secular and religious sciences developed. Mysticism which emerged as a result of this process also played an important role in the socio-spiritual life of society. Sufism is an important component of Muslim philosophy. It is important to study the religious and philosophical doctrine of mysticism in order to assess properly the formation and development of the philosophy of the nation of the East. Sufism deeply ingrained in social and cultural life and had a significant impact on the development of science, culture and literature. The Khojagan, Yassaviya, Kubraviya and Naqshbandi sects of Sufism were formed in Central Asia and spread to other Muslim countries.